Novel Lactotransferrin-Derived Antimicrobial Peptide LF-1 Inhibits the Cariogenic Virulence Factors of Streptococcus mutans - Junyuan Luo; Zening Feng; Xiaohui Lyu; Linglin Zhang (MDPI AG, 2023)
We previously developed a novel lactotransferrin-derived antimicrobial peptide, LF-1, with selective antibacterial activity against the characteristic cariogenic bacterium Streptococcus mutans. This study further investigated the effects of LF-1 on the cariogenic virulence factors of S. mutans and evaluated the changes in virulence-associated enzymes and genes; the viability, acidogenicity, and aciduricity of planktonic S. mutans; and initial colonisation and biofilm formation after treatment with LF-1. The method of qRT-PCR was used to evaluate S. mutans virulence-associated gene expression. LF-1 interfered with the cell viability of S. mutans within 6 h. LF-1 inhibited the acidogenicity and aciduricity of S. mutans, with reduced lactic acid production and survival in a lethal acidic environment, and inactivated lactate dehydrogenase and F1F0-ATPase activity. LF-1 decreased surface-adherent S. mutans within 60 min and inhibited S. mutans biofilm formation, where scanning electron microscopy and confocal laser scanning microscopy showed reduced extracellular matrix and bacteria. LF-1 downregulates S. mutans virulence-associated gene expression. LF-1 inhibited the growth and cariogenic virulence factors of S. mutans in vitro with a reduction in key enzymatic activity and downregulation of virulence-associated gene expression. LF-1 has promising application prospects in the fight against S. mutans and dental caries.